Detection of nasal microbiota in pediatric patients with antrochoanal polyps by TLDA. (March 2020) - Song, Beibei; Zheng, Huiwen; Han, Shujing; Tang, Lixing; Yang, Xiaojian; Chu, Ping; Wang, Pengpeng; Lu, Jie; Ge, Wentong; Ni, Xin
Abstract: Objective: To evaluate and compare the microbiological features in ACPs groups and control subjects in pediatric group, further to explore the potential role of microbial in the etiology of ACPs. Methods: A total of 32 patients with ACPs, and 10 control subjects were enrolled in this study. Demographic datas were collected. The TaqMan low-density array assays were used to detect the microbial of swab specimens and nasal tissue samples from ACPs patients. Results: A total of 15 species were identified in all groups. Of all the species, Mycoplasma pneumoniae was the most common species in ACP patients, but was negative in control group. Of all the viruses detected, Adenovirus positivity was significantly higher in control group than that in ACPs middle meatus on unaffected side, ACPs middle meatus on affected side, and ACPs polypous surface group ( P < 0.05). Cytomegalovirus positivity was significantly higher in control group than that in ACP polypous group ( P < 0.05). Human herpesvirus 6 (HHV-6) was absent in control goup, and positive in ACP middle meatus on affected side was significantly higher than that in ACP polypous surface and ACP polyp group ( P < 0.05). The expression of other microbial differed not significantly in unaffected side, affected side of ACPs, ACPs polypous surface, and ACPs polyp. Conclusions: Mycoplasma pneumoniae was the most common species in ACP patients. Streptococcus pneumonia and Moraxella catarrhalis were the only bacteria detected at certain frequency in nasal polyps and control subjects. Human herpesvirus 6 andMycoplasma pneumoniae may have potential role in the development of ACPs. The isolates rate of microbial differed in middle meatus on unaffected and affected side of ACPs, ACPs polypous surface, ACPs polyp, and their role in the etiology of ACPs need to be further studied.